Radical History in Australia: A Model for Canada? - Friesen, Gerald (Labour / Le Travail, 1991)
The article reviews several books edited by Verity Burgmann and Jenny Lee including "A People's History of Australia Since 1788: Constructing a Culture," "A People's History of Australia Since 1788: Staining the Wattle," and "A People's History of Australia Since 1788: Making a Life."
Keywords: BOOKS -- Reviews; BURGMANN, Verity; LEE, Jenny; Nonfiction; PEOPLE'S History of Australia Since 1788: Constructing a Culture, A (Book); PEOPLE'S History of Australia Since 1788: Making a Life, A (Book); PEOPLE'S History of Australia Since 1788: Staining the Wattle, A (Book)